Increasing Online Purchase Intention Based on The Integration of The Technology Acceptance Model and Theory of Planned Behavior - Nonis , Maria Febriani; Miswanto, Miswanto; Horacio, Amancio; Brito, Sr. Ervinia Martins (International Journal of Management and Digital Business, 2024)
This study aims to integrate TAM and TPB to provide the best model to help predict the online shopping intentions of Shopee marketplace consumers. The sampling techniques in this study combine purposive and snowball sampling, in which 234 respondents were obtained from several islands in Indonesia. This research uses three software for data processing and testing: Microsoft Excel, IBM SPSS Statistics version 26, and IBM AMOS version 24. The findings of this study are: (a) perceived ease of use positively affects attitude, (b) perceived usefulness does not positively affect attitude, (c) perceived ease of use positively affects perceived usefulness, (d) attitude positively affects purchase intention, (e) subjective norms positively affect purchase intention, and (f) perceived behavioral control positively affects purchase intention. The findings indicate that the Technology Acceptance Model and Theory of Planned Behavior can be integrated to provide a better research model for predicting consumer intentions to shop online.